OPTIMIZING PRODUCTIVE ZAKAT FINANCING: THE MODERATING ROLE OF BUSINESS MENTORING ON SUSTAINABLE WELFARE - Ihrom Jaelani; Sari Damayanti; Acim; Misbahul Khoer (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to evaluate the efficacy of productive zakat financing on the creation of sustainable welfare for mustahik (zakat recipients), and to explore the potential moderating role of business mentoring as a behavioral control mechanism. An explanatory quantitative approach was applied to a purposively selected surviving cohort comprising 75 micro-entrepreneurs who received assistance from the National Board of Zakat (BAZNAS) in Ciamis Regency, Indonesia. Data were collected via structured questionnaires and analyzed using Moderated Regression Analysis (MRA), deliberately adopting a mean-centering procedure to mitigate the risks of structural multicollinearity inherent in interaction terms. Baseline linear regression results suggest that productive zakat financing has a significant direct effect on welfare (R2 = 0.695, p < 0.05). Furthermore, the MRA indicates the presence of a moderation effect, wherein business mentoring appears to act as a significant positive moderator (β = 0.040, p = 0.029). The inclusion of this interaction variable increases the model's explanatory power to 85.8% (R2 = 0.858). These findings suggest that Islamic philanthropy regulators may benefit from adopting an integrated incubation ecosystem that systemically bundles capital provision with mentor education. The primary limitation of this study is its inherent susceptibility to survivorship bias, as it evaluates only active business units, combined with a cross-sectional observation design that limits the assertion of definitive causal inferences over extended time horizons. This research highlights a potential paradigm shift in zakat program evaluation by positioning business mentoring not merely as a parallel predictor variable, but as a crucial moderating mechanism that facilitates the attainment of holistic prosperity guided by Maqashid Sharia.